Nivel de depresión en adolescentes de bachillerato de la Unidad Educativa Chilla, periodo 2022-2023 - Ríos Caiminagua, José Alexander (2024)
Depression is a mood alteration that can cause discouragement and little hope for the future; this can occur at all stages of life and more frequently in adolescence, due to a series of physical and psychological changes that occur at this stage, which makes them vulnerable suffering from it. The objective of this research was to characterize the level of depression in adolescents at Unidad Educativa Chilla High School. The methodology of this research was descriptive, quantitative, and cross-sectional, with the participation of 60 high school adolescents from the Unidad Educativa Chilla High School, where the Beck test (BDI-2) was used as an instrument that evaluates depression, taking into account the somatic-motivational and cognitive-affective dimensions. The analysis of the results showed that 38.3% are 17 years old, 51.7% are male, 70% belong to the urban area, 100% are single, while 40% of the participants are in their third year of high school. Concerning the level of depression based on the somatic-motivational dimension, 40% had a minimum level and 11.7% a severe level; likewise, in the cognitive-affective dimension, 43.3% presented a mild level of depression and 1.7% a severe level. Regarding the general level of depression, 33.3% presented a minimum level, followed by a severe level of depression with 26.7% and 18.3% with a mild level. In conclusion, depression is one of the major mental health problems affecting adolescents, especially when it generates alterations in the dimensions of the human being.